2016
DOI: 10.1186/s12939-016-0451-4
|View full text |Cite
|
Sign up to set email alerts
|

A lost tribe in the city: health status and needs of African asylum seekers and refugees in Hong Kong

Abstract: BackgroundHong Kong’s resistance to be a signatory of the 1951 Geneva Convention and lack of domestic policies in this area has resulted in restrictions on access to healthcare amongst asylum seekers and refugees (ASRs). Using social determinants of health framework this study sought to identify health practices, problems and needs of African ASRs in Hong Kong.MethodsA cross-sectional survey comprising of six domains including health status, health-seeking behaviour and social experience targeted at adult Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…28 Another study showed that host governments should have a moral obligation to the health needs of migrants and refugees. 29 Others have called for a strong and coordinated support at the global, national and subnational levels to ensure that refugees remain a priority in societal plans. 30 According to the Asylum Law in Germany, newly arrived refugees must receive a health insurance card that provides them with screening services for some communicable diseases.…”
Section: Discussionmentioning
confidence: 99%
“…28 Another study showed that host governments should have a moral obligation to the health needs of migrants and refugees. 29 Others have called for a strong and coordinated support at the global, national and subnational levels to ensure that refugees remain a priority in societal plans. 30 According to the Asylum Law in Germany, newly arrived refugees must receive a health insurance card that provides them with screening services for some communicable diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This article builds upon recent works on refugee studies that examined the impact of policies and asylum-seeking arrangements on asylum-seekers’ mental health (Ahearn, 2000; Chuah et al, 2018; Coffey et al, 2010; Wong et al, 2016, 2017). Aligned with most of these studies, this research explores the relationship between the social determinants of health and the subjective well-being of asylum-seekers.…”
Section: Security Emotion Religiosity and Subjective Well-beingmentioning
confidence: 99%
“…Like any forcibly displaced migrants, the constant pressure facing the asylum-seekers and refugees in Hong Kong from the threats of deportation, poverty and discrimination may associate with their health and mental well-being. Wong et al [ 7 , 8 ] have published two articles on African asylum-seekers in Hong Kong which highlight discrimination as one of the social determinants of access to health services. Using quantitative survey methods, the two papers provide interesting and invaluable insights on the African ASRs in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…Voluminous research has been conducted on refugees' mental health and factors associated with their psychological well-being in South America, Europe, the USA and Asia, including asylum-seekers and refugees in different situations [ 7 , 8 , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Some focus on specific circumstances such as detention [ 19 , 21 ] or on refugee housing facilities [ 17 ]; some focus on particular issues like access to health services [ 7 , 8 ], the relationship between trauma and post-migration experiences [ 22 ], and the long years living in a host country [ 12 , 20 ]; others focus on pre-migration and/or post-migration experiences [ 15 , 23 ]. In Hong Kong, however, asylum-seekers and refugees are in a particularly transient position, expecting either to be deported back to their home countries should their cases fail, or to be accepted by third countries should their cases be upheld.…”
Section: Introductionmentioning
confidence: 99%